Estrus Synchronization Using Intravaginal Medroxyprogesterone Acetate (MAP), MAP Plus Prostaglandin F2α, Controlled Internal Drug Release (CIDR) or CIDR Plus Prostaglandin F2α in Saanen Dairy Goats in Thailand - Kajaysri, Jatuporn; Thammakarn, Chanathip (Agriculture and Natural Resources, 2012)
The objective of this study was to compare the efﬁ ciency of medroxyprogesterone acetate (MAP) in the form of impregnated intravaginal sponges with or without Prostaglandin F2α (PGF2α) and natural progesterone impregnated controlled internal drug release (CIDR) devices with or without PGF2α in dairy Saanen goats in Thailand. Seventy-ﬁ ve Saanen does were divided into ﬁ ve equal groups. The sixty does in Groups 1 to 4 in Experiment 1 were assigned for estrus synchronization using the following intravaginal progestagen techniques: sponges impregnated with MAP in Group 1 (n=15), sponges with MAP and intramuscular injection of 125 g PGF2α in Group 2 (n=15), progesterone CIDR devices in Group 3 (n=15) and progesterone CIDR devices and intramuscular injection of 125 g PGF2α in Group 4 (n=15). Intravaginal progestagens were administered for 13 d and the PGF2α was injected on day 13. Estrus responses of does in Groups 1 to 4 were detected from 12 to 60 hr after progestagen withdrawal. In the remaining 15 does of Experiment 2 in Group 5, estrus was synchronized by intravaginal progestagen with MAP for 13 d. Estrus responses of does in Group 5 were detected at 24 and 48 hr after progestagen withdrawal. After estrus synchronization, the estrus does in Groups 1 to 5 were artiﬁ cially inseminated with frozen semen once within 48–50 hr after progestagen withdrawal. However, for does in estrus in Group 5, the vaginal mucous accumulations were ﬂ ushed with saline solution before artiﬁ cial insemination (AI). Pregnancy was detected by ultrasonography on day 60 after AI. The result of Experiment 1 was estrus responses in all does in Groups 1, 2 and 4 but in only 10 does in Group 3. The mean estrus onset times of Groups 1 and 2 were not signiﬁ cantly different (21.0 ± 1.2 and 21.5 ± 1.3 hr, respectively) but were signiﬁ cantly different from those of Groups 3 (18.5 ± 1.9 hours) and 4 (18.6 ± 2.0 hr) (P < 0.05). The mean estrus durations of Groups 1 to 4 were not signiﬁ cantly different. Pregnancy ultrasonography revealed no difference in the pregnancy rates among Groups 1 to 4. Experiment 2 resulted in estrus responses in all does in Group 5. Comparison of the pregnancy rates of Groups 1 and 5 showed that Group 5 had a trend of a higher pregnancy rate than Group 1. It can be concluded that the MAP treatment with or without PGF2α had equal efﬁ cacy to the CIDR-with-PGF2α treatment, and that the MAP treatment combined with vaginal mucous ﬂ ushing could possibly increase the conception rate.